Kombinasi Metode RSA, Secret Sharingasmuth-Bloom Dan Redundant Pattern Encoding Untuk Mengamankan Pesan - Zairy Lubis, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The combination of algorithms is the process of combining more than one algorithm so that the resulting level of security is better. This study combines 3 direct algorithms so that the level of defense in data security is more optimal. The combined algorithms in this study are the RSA algorithm, secret sharing asmuth-bloom, and redundant pattern encoding. This study describes how the procedure is carried out to combine the three algorithms above, namely RSA, secret sharing asmuth-bloom, and redundant pattern encoding. The combination process is carried out in stages by carrying out the encryption process using RSA first, then the results of the encryption are encrypted again using secret sharing asuth-bloom, resulting in a new ciphertext and then the new ciphertext is inserted into an image using the redundant pattern encoding method. The result of this study is to design a data-based security application using a combination of the RSA algorithm, secret sharing asmuth-bloom, and redundant pattern encoding. This application can be used to secure data in the form of text, so that it cannot be taken by others. In addition, the application that will be designed is easier to use in data security.